Demographic, clinical and laboratory characteristics of adult-onset minimal change disease in Turkey: Turkish Society of Nephrology-Glomerular Diseases (TSN-GOLD) Working Group - Aydın, Zeki; Yılmaz, Mürvet; Sipahioğlu, Murat; Dervişoğlu, Erkan; Aydemir, Nihal; Uzun, Sami; İstemihan, Zülal; Ünsal, Oktay; Tatar, Erhan; Berktaş, Hacı Bayram; Özdemir, Arzu; Şumnu, Abdullah (Springer, 2023)
Purpose In our study, diagnostic and demographic characteristics of patients diagnosed with minimal change disease (MCD) by biopsy, clinical and laboratory findings in our country were investigated. Methods Data were obtained from the Turkish Society of Nephrology Glomerular Diseases (TSN-GOLD) Working Group database. Demographic characteristics, indications for biopsy, diagnosis of the glomerular diseases, comorbidities, laboratory and biopsy findings of all patients were recorded. The data presented are cross-sectional and includes application data for the biopsy period. Results Of 3875 patients, 233 patients with MCD (median age 35.0 years) were included in the study, which constitutes 6.0% of the total glomerulonephritis database. Renal biopsy was performed in 196 (84.1%) patients due to nephrotic syndrome. Median serum creatinine was 0.7 (0.6-1.0) mg/dl, mean eGFR was 104 +/- 33 ml/min/1.73 m(2) and median proteinuria 6000 mg/day. The number of patients under the age of 40 years was 139 (59.7%) (Group A), and the number of patients aged 40 years and over was 94 (40.3%) (Group B). Compared to Group A, global sclerotic glomeruli (24 vs. 43, p < 0.001) interstitial inflammation (15 vs. 34, p < 0.001), interstitial fibrosis (20 vs. 31, p = 0.001, vascular changes (10 vs. 25, p < 0.001) and tubular atrophy (18 vs. 30, p < 0.001) were found to be significantly higher in Group B. There was no difference in immunofluorescent staining properties between the two groups. Conclusion Our data are generally compatible with the literature. Chronic histopathological changes were more common in patients aged 40 years and older than younger patients. Studies investigating the effects of these different features on renal survival are needed.
Keywords: Primary Glomerular Diseases; Minimal Change Disease; Nephrotic Syndrome